Pengaruh Karakteristik Pekerjaan Dan Stres Kerja Terhadap Keinginan Pindah Tempat Kerja Pada Pekerja Proyek Konstruksi - Fajar Susilowati; Tri Widya Swastika (Jurnal Poli-Teknologi, 2020)
Human resources are seen as an essential asset in a company because man is a dynamic resource and always needed in every process of production of goods and services. Therefore, this research was performed to analyze the influence of Jobs’ Characteristics and Work Stress on Turnover Intention. This research uses Quantitative Data by Questionnaire Method. The result of data processing shows that Work Stress has a stronger influence on Turnover Intention than Jobs Characteristics. Both of these variables impact amounted to 0.65 of the employee turnover intentions. It can calculate that determination coefficient 42.3%, which means that the variable Jobs Characteristic and Work Stress have contributed amounted to 42.3% of the employee turnover intentions, while other variables determine 57.7%. The indicator most influence on turnover intention in construction employees was the differences in value between the company and its employees.